The Arts, Loose Parts and Conversations - Smith-Gilman, Sheryl (Journal of the Canadian Association for Curriculum Studies, 2018)
Educators today are being asked to design curricula whereby learners’ abilities to analyze, question, problem-solve, evaluate and reflect are being provoked. The quest lies in uncovering suitable teaching approaches that will allow critical thinking skills to emerge organically and meaningfully. I argue that an integration of loose parts can offer a methodology and a provocation that makes way for open-ended, divergent and creative thinking skills to be activated. “Loose parts” can be open-ended materials that are manipulated, designed, dismantled and reconstructed in multiple ways. I also see “loose parts” as a mindset, a process-oriented approach whereby meaningful conversations emerge unexpectedly and add significantly to learning. This article presents two stories to show how arts-based approaches and mindfulness to loose parts can unearth thought-filled and caring conversations. The discussion is inspired and written via a reflective lens of personal encounters, first, in a longitudinal research project with young children in an Indigenous First Nations Community, and, second, with preservice teachers in a university class. It is within these periods that students, teachers and families were impacted by loose parts whereby materials and conversations made way for new perspectives in understanding the world.